Efektivitas Penerapan Pemenuhan Proses Penyidikan Perkara Anak di Kepolisian Daerah Bali - I Putu Gde Asmara Perdana; Luh Nila Winarni; Cokorde Istri Dian Laksmi Dewi (Jurnal Studi Multidisiplin Ilmu, 2023)
Purpose: The purpose of this study was to determine and analyze the effectiveness of the application of the fulfillment of the case investigation process of children in the Bali Regional Police. The delinquency of children, which they sometimes considered normal, often caused these children to commit crimes that violated the law. As a child in conflict with the law, often the child's rights are not protected. The majority of children in conflict with the law claim to have experienced acts of violence while at the police station. Methodology: In this research, a sociology of law approach is used, meaning that it examines issues raised with facts supported by a juridical approach. Results: The results of the study show the effectiveness of the diversion process in which perpetrators and victims meet face to face, internationally referred to as "Restorative Justice". However, the juvenile justice system in Indonesia has not been effective, because the idea of diversion is not easy to implement. We cannot catch a child, because it can damage a child's mental. Government support in raising public awareness related to this diversion must be increased in the form of socialization. In addition, it is necessary to raise awareness of advocates and correctional institutions in order to act wholeheartedly in helping the police to pursue criminal cases committed by bad children.